Regional diversification of cultural sector potential in Poland - Namyślak Beata (Bulletin of Geography. Socio-Economic Series)
The article presents an assessment of the potential of the cultural sector in Poland from a regional perspective. The author analysed statistical data from 2005–2017 on changes in demand for selected cultural products and services. A conclusion was reached using linear sequencing, which aimed to establish a value for a synthetic indicator showing the situation of the cultural sector in the regions. This indicator was calculated on the basis of characteristics referring to cultural infrastructure resources, cultural activities, cultural expenditure and income in the cultural sector. In the obtained list of regions, the highest places were achieved by the Lubelskie, Zachodniopomorskie and Dolnośląskie voivodships. The weakest result was achieved by the Świętokrzyskie Voivodship. However, the scores obtained were generally low – none of the regions achieved high scores in all partial values. Considering the relatively small differences between the values of the indicator, it is possible that the obtained picture will change due, among others, to the high dynamics of changes in expenditures being incurred in the cultural sector.